2001
DOI: 10.1007/s10228-001-8153-2
|View full text |Cite
|
Sign up to set email alerts
|

Channa siamensis (Günther, 1861), a junior synonym of Channa lucius (Cuvier in Cuvier and Valenciennes, 1831)

Abstract: The holotype of Channa siamensis (Günther, 1861) was examined and compared with specimens of all other channid species currently considered to be valid (2 genera, 27 species). As all of the examined morphological characters (meristics, morphometrics, coloration, a patch of gular scales, and cephalic sensory pores) of the smallsized hototype (74.2 mm SL) agree with those for C. lucius except for slight gaps in predorsal length and interorbital width (subject to allometric changes), the authors concluded that C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Musikasinthorn and Taki (2001) divided the Channidae into two major groups by presence or absence of a patch of scales at the chin (gular) region, which they called gular scales (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Musikasinthorn and Taki (2001) divided the Channidae into two major groups by presence or absence of a patch of scales at the chin (gular) region, which they called gular scales (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Recent taxonomic studies have discovered several new channid species and found unique morphological characters that are common among some species (e.g., Musikasinthorn, 1998Musikasinthorn, , 2000Musikasinthorn and Taki, 2001;Zhang et al, 2002). However, to the best of our knowledge, phylogenetic relationships among the channid species have been rarely studied, whether morphologically or molecularly.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Channids are more diverse in Asia, 23 species, all included in the genus Channa Scopoli (see Musikasinthorn, 2000;Musikasinthorn and Taki, 2001), currently being considered as valid. From Africa, only 3 species are recognized, all being included in the genus Parachanna Teugels and Daget (see Bonou and Teugels, 1985;Teugels, 1992).…”
Section: Diagnosis a Species Ofmentioning
confidence: 99%
“…1) was captured with a pulsed direct current (DC) (350-600 V, 12 kW, 0-100 impulses per second) and was identified according to Musikasinthorn and Taki (2001) and Courtenay and Williams (2004). The fish was 76.5 cm long (TL) and weighed 5.8 kg.…”
mentioning
confidence: 99%